2008
DOI: 10.1021/la7032675
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Organization in SAMs Used for Neuronal Cell Growth

Abstract: The attachment of cells onto solid supports is fundamental in the development of advanced biosensors or biochips. In this work, we characterize cortical neuron adhesion, growth, and distribution of an adhesive layer, depending on the molecular structure and composition . Neuronal networks are successfully grown on amino-terminated alkanethiol self-assembled monolayer (SAM) on a gold substrate without adhesion protein interfaces. Neuron adhesion efficiency was studied for amino-terminated, carboxy-terminated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…Many cell types have been successfully patterned with microfluidics [14][15][16], lCP [17], inkjet printing [18,19], plasma treatment [20], self-assembled monolayers [21][22][23][24], self-assembled constructs [25], laser scanning lithography [26], atomic force microscope lithography, dip-pen nanolithography [27], topography [28,29], carbon nano-tubes [30], or their combinations [31,32]. Neurons are, however, distinctive cells with highly polarized morphology, much smaller somata, and thus few anchoring points for adhesion in comparison to most types of adherent mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Many cell types have been successfully patterned with microfluidics [14][15][16], lCP [17], inkjet printing [18,19], plasma treatment [20], self-assembled monolayers [21][22][23][24], self-assembled constructs [25], laser scanning lithography [26], atomic force microscope lithography, dip-pen nanolithography [27], topography [28,29], carbon nano-tubes [30], or their combinations [31,32]. Neurons are, however, distinctive cells with highly polarized morphology, much smaller somata, and thus few anchoring points for adhesion in comparison to most types of adherent mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Forster et al (18) reported the photosubstitution of chlorido for aqua ligands in an Ru(II) polypyridyl complex, [Ru(bpy) 2 (4-pyridyl)ethylene]. The complex forms well-defined SAMs and undergoes loss of either the bpe anchoring ligand or the chlorido ligand, depending on the solvent employed, with aqueous solvents favoring the substitution of the latter ligand.…”
Section: Photochemically Reactive Self-assembled Monolayers: Irreversmentioning
confidence: 99%
“…Smart surfaces, surfaces that can respond to a specific external stimulus in a specific manner, are of increasing interest in areas as diverse as cell culture (1,2), microfluidics (3,4), organic electronics (5), and coatings (6,7). When combined with the flexibility provided through molecular synthesis, supramolecular chemistry, and surface science, exciting opportunities emerge toward the development of smart molecular materials and devices.…”
Section: Introductionmentioning
confidence: 99%
“…The growth and adhesion of cortical neurons on self-assembled monolayers depends on the functional groups for amino-terminated, carboxyterminated and 1:1 mixed alkanethiol monolayers on gold, as described by Palyvoda et al [169]. Using SFG they inferred that the ordering of the terminal amino groups does not affect the ability for neuron adhesion, while the dissociation of carboxylic groups hampers neuron attachment.…”
Section: Probing Surface Functionalizationmentioning
confidence: 99%